Risk Assessment of Harmful Algal Blooms in Salmon Farming: Scotland as a Case Study - Fatima Gianella; Michael T. Burrows; Keith Davidson (Toxins)
This study explored harmful algal bloom (HAB) risk as a function of exposure, hazard and vulnerability, using Scotland as a case study. Exposure was defined as the fish biomass estimated to be lost from a bloom event, based on the total recorded annual production. Hazard was estimated from literature-reported bloom events. Vulnerability was calculated from records of the number of employees (2020), as an estimate of aquaculture-based employment. The dinoflagellate Karenia mikimotoi was identified as the HAB species with the highest frequency of reported bloom events in Scotland, with variable spatial and temporal reports, but environmental and climatological variables regulating these events are currently unknown. The Shetland Islands region exhibited the highest combined HAB risk, with the highest scores in all three components. Vulnerability was particularly important to overall risk within an island setting, where a larger proportion of the population was dependent on aquaculture. The analysis demonstrated the potential to evaluate the economic and social consequences of HAB events on the aquaculture industry. As fish-killing HABs and fish health impacts are likely under-reported, more transparent reporting of events and related fish health and physiological consequences is recommended for a more quantitative application of this approach.